Effect of Different Doses of Intrathecal Dexmedetomidine as an Adjuvant Combined With Hyperbaric Ropivacaine in Patients Undergoing Cesarean Section - Bi, Yong-hong; Wu, Jia-min; Zhang, Yan-zhuo; Zhang, Rui-qin (Frontiers in Pharmacology, 2020)
Objective: In this study, we aim to investigate the effect of different doses of dexmedetomidine as an adjuvant to hyperbaric ropivacaine in spinal anesthesia for cesarean section. Methods: Seventy-five parturients with American Society of Anesthesiologists(ASA) I or II were anesthetized with intrathecal ropivacaine (12.5 mg) alone (R group) or in combination with dexmedetomidine 3 μg (RD3 group) and 5 μg (RD5 group) to undergo a cesarean section. The anesthetic parameters, postoperative analgesia, stress responses and neonates outcomes were monitored. Results: The onset time of sensory block to T10, T4, and peak level in the RD3 group and RD5 group were significantly shorter than those in the R group (p<0.05). The time of the level of sensory block to descend two segments and to T10 in the RD3 group(57.28±16.65min, 3.87±1.60h) and RD5 group(71.92±10.10min, 3.99±1.06h) were longer than that in the R group(40.64±12.06min, 1.98±1.01h) (p<0.05). The median time of motor blockade to both legs score 3 on the Bromage scale(B3B3) in the RD3 group and RD5 group was shorter than that in the R group( p<0.001). The time of motor blockade recovery to both legs score 0 on the Bromage scale(B0B0) in the RD5 group(3.6h) was longer than that in the R group(2h) or RD3 group(2.2h) (p<0.001). Visceral traction response and abdominal muscle relaxation during the operation in the RD3 group and the RD5 group were better than that in the R group. The Visual Analogue Score(VAS) in the 12h after the operation in the RD3 group(3.30±1.17) and RD5 group(2.80±0.87) was smaller than that in the R group(3.80±1.47) (p<0.05). The incidence of shivering in the RD3 group and RD5 group was significantly lower than that in the R group (p<0.05). The postoperative concentrations of c-reactive protein(CRP), interleukin-6(IL-6) and cortisol in the RD3 and RD5 groups were lower than those in the R group (p<0.05). Conclusion: 3 µg intrathecal dexmedetomidine as an adjuvant to ropivacaine improved intraoperative somato-visceral sensory block characteristics and postoperative analgesia, alleviated shivering in parturients, and did not prolong the time of motor block or produce any side effects, which makes this dose appropriate for cesarean delivery.